Aplicação do Balanced Scorecard na avaliação de desempenho em hospitais - Renesto, José Carlos (2008)
The current work has the purpose to demonstrate as to evaluate the performance of strategy of the hospital, being used the balanced marker. It is research of the explorer, based a case study, in a qualitative perspective. Elaborated proposted it includes strategical, indicating and objective objectives of performance, distributed in the four perspectives, and a strategical map. After the experience, the results of the evaluation had been synthecized in the strategical map. He was verific that the use of the balanced marker leads the critical company to the optimização of its management, aids the identification of the chances and factors with the relation of employees' satisfaction with the efficiency of the process to keep next customers; it also, aids the communication in the company and management of the parts, since that it induces question and the formularization of punishment and dynamic. The focus in becoming it strategy, since that for the balanced marker, it allows at each moment the verification of the critical aspects of the institution. This work is introduced in the line of the research of the Pontifical University Catholic of São Paulo